2018
DOI: 10.3390/jcm7120507
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Fracture Risk of Osteoporosis in Patients with Rheumatoid Arthritis: A Multicenter Comparative Study of the FRAX and WHO Criteria

Abstract: (1) Background: We evaluated the prevalence and fracture risk of osteoporosis in patients with rheumatoid arthritis (RA), and compared the fracture risk assessment tool (FRAX) criteria and bone mineral density (BMD) criteria established by the World Health Organization (WHO). (2) Methods: This retrospective cross-sectional study, which included 479 RA patients in 5 hospitals, was conducted between January 2012 and December 2016. The FRAX criteria for high-risk osteoporotic fractures were calculated including a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 27 publications
2
25
0
1
Order By: Relevance
“…It integrates the risks associated with BMD at the femoral neck as well as clinical risk factors such as age, height, weight, sex, smoking status, alcohol drinking, use of glucocorticoids, and history of secondary osteoporosis. FRAXtool ® is useful to set a threshold in order to screen candidates for pharmacological intervention and the proportion of RA patients with a greater risk of osteoporotic fractures detected with FRAXtool ® is higher than with the WHO criteria [ 19 ]. When applied to 238 patients enrolled in the Canadian Early Arthritis Cohort (CATCH) study without using BMD measurements, FRAXtool ® identified 5% to 13% of patients at a high risk for fracture [ 49 ].…”
Section: Epidemiology Of Bone Loss and Fractures In Rheumatoid Patmentioning
confidence: 99%
See 2 more Smart Citations
“…It integrates the risks associated with BMD at the femoral neck as well as clinical risk factors such as age, height, weight, sex, smoking status, alcohol drinking, use of glucocorticoids, and history of secondary osteoporosis. FRAXtool ® is useful to set a threshold in order to screen candidates for pharmacological intervention and the proportion of RA patients with a greater risk of osteoporotic fractures detected with FRAXtool ® is higher than with the WHO criteria [ 19 ]. When applied to 238 patients enrolled in the Canadian Early Arthritis Cohort (CATCH) study without using BMD measurements, FRAXtool ® identified 5% to 13% of patients at a high risk for fracture [ 49 ].…”
Section: Epidemiology Of Bone Loss and Fractures In Rheumatoid Patmentioning
confidence: 99%
“…When applied to 238 patients enrolled in the Canadian Early Arthritis Cohort (CATCH) study without using BMD measurements, FRAXtool ® identified 5% to 13% of patients at a high risk for fracture [ 49 ]. Patients with a higher osteoporotic fracture risk determined by FRAXtool ® are more likely to be female, especially postmenopausal women, with alcohol use, glucocorticoid use, proton pump inhibitor use, and had lower BMI (<25 kg/m 2 ) [ 19 ]. High fracture risk patients identified by the FRAXtool ® was also statistically associated with disease duration, menopause duration, disease activity score (DAS28), and health assessment questionnaire (HAQ) [ 25 ].…”
Section: Epidemiology Of Bone Loss and Fractures In Rheumatoid Patmentioning
confidence: 99%
See 1 more Smart Citation
“…15 A growing body of evidence over the last years revealed an excessive burden of both CVD and impaired bone health in patients with systemic autoimmune disorders. [16][17][18] For instance, in SLE, heightened rates of both subclinical atherosclerosis, 16 osteoporosis as well as peripheral and vertebral fractures have been repeatedly reported. 19 20 Moreover, low 25-OHD levels (<20 ng/mL) were found to be prevalent in patients with SLE .…”
Section: Introductionmentioning
confidence: 99%
“…Возможность применения в клинической практике FRAX ® без введения дополнительной информации о МПК подтверждают исследования, в которых в различных популяциях и на разных группах пациентов значения риска перелома, полученные с помощью данного инструмента с введением данных МПК и без них, хорошо коррелировали между собой [15][16][17][18]. Однако определение риска перелома без МПК дает более высокий результат, чем его вычисление с учетом данных денситометрии шейки бедра как в популяции, так и среди больных РА, что может приводить к завышенной оценке риска перелома у конкретного пациента [19][20][21][22]. Так, например, в когорте 50 датских женщин с РА (средний возраст -63,6±11,7 года) добавление величины Т-критерия шейки бедренной кости уменьшило средние значения 10-летнего абсолютного риска перелома с 25,8±18,6 до 22,9±15,8% [19].…”
Section: результатыunclassified